Taxonomically Restricted Genes Are Fundamental to Biology and Evolution - Johnson, Brian R. (Frontiers in Genetics, 2018)
Genes limited to particular clades, taxonomically restricted genes (TRGs), are common in all sequenced genomes. TRGs have recently become associated with the evolution of novelty, as numerous studies across the tree of life have now linked expression of TRGs with novel phenotypes. However, TRGs that underlie ancient lineage specific traits have been largely omitted from discussions of the general importance of TRGs. Here it is argued that when all TRGs are considered, it is apparent that TRGs are fundamental to biology and evolution and likely play many complementary roles to the better understood toolkit genes. Genes underlying photosynthesis and skeletons, for example, are examples of commonplace fundamental TRGs. Essentially, although basic cell biology has a highly conserved genetic basis across the tree of life, most major clades also have lineage specific traits central to their biology and these traits are often based on TRGs. In short, toolkit genes underlie what is conserved across organisms, while TRGs define in many cases what is unique. An appreciation of the importance of TRGs will improve our understanding of evolution by triggering the study of neglected topics in which TRGs are of paramount importance.